Evaluating social-welfare expenditures - how well does the system perform in reducing poverty - Callan, T; Nolan, B (Economic & Social Studies, 1989)
The results of the ESRI Survey of Income Distribution, Poverty and Usage of State services are used to assess the success of the Irish social welfare system in alleviating poverty. About 10 per cent of persons are found to fall below the safety-net income level provided by the system, many of whom are apparently entitled to but not taking up income support. Evaluating the system in terms of its effectiveness in bringing people up to independently-derived relative income standards, about 70-80 per cent of the pre-transfer poverty gap was eliminated by social welfare payments. The percentage of spending on transfers which goes towards bringing people up to the poverty line varied between 54 per cent and 77 per cent depending on the standard chosen. The Irish system appears rather less effective in reducing poverty than those of some other developed countries. Spending on contributory, as well as means-tested, schemes is quite highly concentrated towards the bottom of the income distribution, limiting the scope for reallocation. This is less true of Child Benefit. Rationalisation of the payment structure could increase the effectiveness of the system in alleviating poverty, though at current overall spending levels this would not be sufficient to bring everyone up to the highest of the relative poverty.
Keywords: Poverty - Ireland; Social welfare expenditure - Ireland